2013
DOI: 10.1071/ah12168
|View full text |Cite
|
Sign up to set email alerts
|

The impact of care recipient falls on caregivers

Abstract: Falls among care recipients have a significant impact on carers, including an increased fear of falling, prompting the need for even closer vigilance. WHAT IS KNOWN ABOUT THE TOPIC? Falls are a significant problem for older people as one in three older people fall each year and injurious falls are the leading cause of injury-related hospitalisation in older people. In Australia falls cost the economy over $500 million per year. WHAT DOES THIS PAPER ADD? This paper adds a unique perspective to the falls literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 15 publications
1
41
0
2
Order By: Relevance
“…A prospective study of 96 pairs of carers and care recipients in Melbourne, Australia, found that carers reported a significant increase in caregiver burden after the older person had had their first fall. (8) Similar results were also found in a large crosssectional study of 1,874 community-dwelling older persons in Japan. (9) In this study, a history of falls in the person being cared for was associated with increased caregiver burden, even after controlling for functional status and comorbidities.…”
Section: Fall Concern Among Carerssupporting
confidence: 73%
See 3 more Smart Citations
“…A prospective study of 96 pairs of carers and care recipients in Melbourne, Australia, found that carers reported a significant increase in caregiver burden after the older person had had their first fall. (8) Similar results were also found in a large crosssectional study of 1,874 community-dwelling older persons in Japan. (9) In this study, a history of falls in the person being cared for was associated with increased caregiver burden, even after controlling for functional status and comorbidities.…”
Section: Fall Concern Among Carerssupporting
confidence: 73%
“…(8) Older people can require higher levels of care following falls or progression of illness that causes falls. (8) Among Asian carers in general, societal expectations of filial piety can serve as both a motivator for caregiving and a cause of stress among those who feel that they are unable to fulfil this role.…”
Section: Abstract: Carers Fall Concern Fall Prevention Older Persomentioning
confidence: 99%
See 2 more Smart Citations
“…Falls are a risk factor themselves, as the person who has fallen is prone to fall again within a year (Todd & Skelton, 2004), and falls put a strain on the family. It has been found that the burden of care is greater for family caregivers (Maggio et al, 2010), caregiving alters their lives (Dow, Meyer, Moore, & Hill, 2013) and affects their quality of life (Roth, Perkins, Wadley, Temple, & Haley, 2009).…”
Section: Introductionmentioning
confidence: 99%